Kinematic Analysis of SAVGS - Samnang Chheang; Unggul Wasiwitono (Institut Teknologi Sepuluh Nopember, 2020)
The SAVGS as active low bandwidth retrofitted in the double-wishbone arrangement is studied. In this study, two configurations of arm linkages and variations of single-link are investigated. A linear equivalent model of the quarter car is presented based on energy conservation principles. The estimated results captured that the spring stiffness and damping coefficients of the equivalent model behave smaller when lengthening the lower arm geometry. On the other hand, the spring stiffness, damping coefficients, and linear actuator speed of the equivalent model increase when lengthening the single-link.